The natural agent 4-vinylphenol targets metastasis and stemness features in breast cancer stem-like cells - Leung, Hoi-Wing; Herr, Ingrid (Cancer chemotherapy and pharmacology, 2018)
Background and purpose: Cancer stem-like cells (CSC) are regarded as the source of tumour origins, metastasis and drug resistance, and limits current treatment regimens. Previously, we reported the first study of the anti-angiogenic and anti-tumour activities of 4-vinylphenol. To further examine the therapeutic role of 4-vinylphenol, the inhibitory effects of 4-vinylphenol on cancer stemness, drug resistance and metastasis in breast cancer were investigated in the present study. Study design and methods: We enriched parental MDA-MB-231 cells with CSCs in serum-free medium to give spheroids. The effects of 4-vinylphenol on cancer stemness, metastasis and drug resistance in CSC-enriched MDA-MB-231 cells were studied in vitro and in vivo. Results: CSC-enriched MDA-MB-231 cells demonstrated higher tumorigenic and metastatic potential. 4-Vinylphenol reduced spheroid formation and ALDH1 expression in CSC-enriched cultures, revealing its inhibitory effects on the traits of CSCs. 4-Vinylphenol suppressed colony formation and cell proliferation. 4VP also inhibited in vitro invasion and in vivo metastasis in zebrafish model. Our results showed that it reduced vimentin expression, suppressed cell migration, affected the expression and/or activity of MMPs, TIMPs and uPA. In addition, the expressions of caspases 3 and 9 were increased upon its treatment, and surprisingly, prolonged treatment did not confer cancer cells with drug resistance to 4-vinylphenol. 4-Vinylphenol probably exhibited its anti-cancer activities via beta-catenin, EGFR and AKT signaling pathways. Conclusion: 4-Vinylphenol was shown to inhibit metastasis and cancer stemness in CSC-enriched breast cancer cells. Since conventional therapies not targeting CSCs possibly lead to failure to eliminate cancer, 4-vinylphenol is a highly potential therapeutic agent for breast cancer patients.
Gesehen am 27.02.2020